If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 5) + 2x = 11 Reorder the terms: -3(5 + x) + 2x = 11 (5 * -3 + x * -3) + 2x = 11 (-15 + -3x) + 2x = 11 Combine like terms: -3x + 2x = -1x -15 + -1x = 11 Solving -15 + -1x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -1x = 11 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = 11 + 15 -1x = 11 + 15 Combine like terms: 11 + 15 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| b=-4a-2c+p | | -2x^2+4x+6=15 | | 8ln(x+5)-7ln=x | | -(3+62b-22+4)= | | 20-y=13 | | 121x^2+9=0 | | 5.00x+.15+2.36=x | | 2x+17=0 | | 0.11m+10=23.20 | | (52+13)b-4= | | 0.50x+15=33.00 | | 3x^2+4x-95=0 | | 2x+4x+1=4 | | 3b-(3b-24)b*3= | | 0.18x+0.7=0.04 | | 14x+12=13x+5 | | 0.9+2.3=-5.8 | | 3x+14=38-5x | | 4y^2-7y-15=0 | | t^2+2t-19=5 | | 0.6x+4=8.2 | | 4x+9=11x-3x | | 6x^2-4x-3=y | | -8k+6k=14 | | -(7y+4)-(-6y-6)=0 | | 8(3x-7)=4(6x+5) | | 8x^2+12=35x | | -3-0= | | 8+3y-6=8y+4-4y | | 3x^2+8x+14=0 | | 30+5x=20x | | y-4=-4(x-5) |